Clinical Randomized Comparison of Medetomidine and Xylazine for Isoflurane Balanced Anesthesia in Horses - Wiederkehr, Alexandra; Barbarossa, Andrea; Ringer, Simone K.; Jörger, Fabiola B.; Bryner, Marco; Bettschart-Wolfensberger, Regula (Frontiers in Veterinary Science, 2021)
To assess drug plasma levels, preanaesthetic sedation, cardiopulmonary effects during anaesthesia and recovery in horses anaesthetized with isoflurane combined with medetomidine or xylazine. Study design Prospective blinded randomized clinical study. Animals Sixty horses undergoing elective surgery. Methods Thirty minutes after premedication (antibiotics, NSAID, acepromazine) horses received medetomidine 7 µg kg-1 (group MED) or xylazine 1.1 mg kg-1 (group XYL) slowly intravenously (IV) and sedation was assessed. Anaesthesia was induced with ketamine/diazepam and maintained with isoflurane in oxygen/air and medetomidine 3.5 µg kg-1 hour-1 or xylazine 0.69 mg kg-1 hour-1. Ringer’s acetate 10 mL kg-1 hour-1 and dobutamine were administered to maintain normotension. All horses were mechanically ventilated to maintain end-tidal carbon dioxide pressures at 45 +/- 5 mmHg (5.3 - 6.7 kPa). Heart rate (HR), invasive arterial blood pressures, inspired and expired gas compositions, pH, arterial blood gases, electrolytes, lactate and glucose were measured. For recovery all horses received intramuscular morphine 0.1 mg kg-1 and medetomidine 2 µg kg-1 or xylazine 0.3 mg kg-1 IV. Recovery was timed and scored using three different scoring systems. Plasma samples to measure medetomidine and xylazine concentrations were collected at predetermined timepoints. Repeatedly measured parameters were analysed using a two-way repeated-measures analysis of variance for differences between groups and over time; p < 0.05 significant. Results Mean arterial blood pressures (MAP) stayed within predetermined ranges but were higher in group XYL despite significant lower dobutamine doses. Other measured parameters were within clinically acceptable ranges. Plasma levels were at steady state during anaesthesia (MED 2.194 ± 0.073 ; XYL 708 ± 18.791 ng / ml). During recovery lateral recumbency (MED 42.7 ± 2.51; XYL 34.3 ± 2.63 minutes) and time to standing (MED 62.0 ± 2.86; XYL 48.8 ± 3.01 minutes) were significantly shorter in group XYL compared to group MED. Recovery scores did not differ significantly between groups. Conclusion and clinical relevance There were minor differences in arterial blood pressures, of questionable clinical relevance, but recovery times following xylazine were shorter compared to medetomidine, whilst quality of recovery was identical.